This much is true - Margolyes, Miriam 1941- (John Murray, 2021)
"BAFTA-winning actor, voice of everything from Monkey to the Cadbury's Caramel Rabbit, creator of a myriad of unforgettable characters from Lady Whiteadder to Professor Sprout, MIRIAM MARGOLYES, OBE, is the nation's favourite (and naughtiest) treasure. Now, at the age of 80, she has finally decided to tell her extraordinary life story - and it's well worth the wait. Find out how being conceived in an air-raid gave her curly hair; what pranks led to her being known as the naughtiest girl Oxford High School ever had; how she ended up posing nude for Augustus John as a teenager; why Bob Monkhouse was the best (male) kiss she's ever had; and what happened next after Warren Beatty asked 'Do you fuck?' From declaring her love to Vanessa Redgrave to being told to be quiet by the Queen, this book is packed with brilliant, hilarious stories. With a cast list stretching from Scorsese to Streisand, a cross-dressing Leonardo di Caprio to Isaiah Berlin, This Much Is True is as warm and honest, as full of life and surprises, as its inimitable author"--Publisher's description
Keywords: Margolyes, Miriam -- 1941-; Margolyes, Miriam; Motion picture actors and actresses / Great Britain / Biography; Lesbian actresses / Great Britain / Biography; Women television personalities / Great Britain / Biography; Television personalities / Great Britain / Biography; Lesbian actresses; Motion picture actors and actresses; Television personalities; Women television personalities; Great Britain; Autobiographies; Biographies; Autobiografie